A posthuman decentring of person-centred care. Issue 3 (2nd September 2021) - Gibson, Barbara E.; Fadyl, Joanna K.; Terry, Gareth; Waterworth, Kate; Mosleh, Donya; Kayes, Nicola M.
ABSTRACT: In this paper, we examine person-centred care through a Deleuzian posthuman lens with the aim of exploring what becomes possible when the concepts of both person and care are de-centred . We do so through a consideration of the sets of relations that produce 'the client' in health care contexts. Our analysis maps particular entangled material-semiotic forces producing 'M/michael', a young man with a diagnosis of Duchenne muscular dystrophy, within a rehabilitation clinic. Drawing on Deleuzian notions of assemblage, affect, and becoming we explore 'person-care' as an active production that dynamically enacts persons-as-clients through clinical arrangements. Persons are thus reconceptualised in terms of locally produced subject positions and their care relations, rather than pre-existing beings who can be 'centred' within health services. Paradoxically, by de-centring persons and care, we work to conjure ways to strengthen the aspirations of person centredness to humanise health practices. In doing so, we consider different possibilities for re-imagining clinical work and contribute to debates regarding how healthcare conceptualises and addresses disability, health, and wellbeing. We suggest that such posthuman analyses can open up new ways of understanding and re/forming healthcare.